Subclinical hypothyroidism in pediatric nephrotic syndrome: the correlations with albumin, globulin, and proteinuria - Erni Nuraeni; Faiisal Faisal; Ahmedz Widiasta; Novina Novina (Paediatrica Indonesiana, 2020)
Background Nephrotic syndrome causes loss of medium-sized plasma proteins and binding proteins, resulting in thyroid hormone deficiency. Objective To assess for potential correlations between subclinical hypothyroidism in pediatric nephrotic syndrome with albumin, globulin, and proteinuria. Methods This cross-sectional study was conducted in the Department of Pediatrics, Hasan Sadikin General Hospital, Bandung, West Java. All types of nephrotic syndrome patients aged 1 month to < 18 years were included. Blood and urine specimens were collected from the patients for albumin, globulin, thyroid function (T3, fT4 and TSH), and proteinuria tests and analyzed with standard techniques. Results There were 26 subjects, 20 males and 6 females. Ten subjects developed subclinical hypothyroidism, with mean albumin and thyroid-stimulating hormone (TSH) levels of 0.92 g/dL and 6.9 mIU/L, respectively. There was a negative correlation between albumin level and subclinical hypothyroidism (rpb=-0.702; P<0.001) and a positive correlation between proteinuria and subclinical hypothyroidism (r=0.573; P=0.003). Univariate logistic regression analysis revealed that globulin had no impact on the presence of subclinical hypothyroidism, but albumin and proteinuria did have such an impact. The odds ratios of albumin and proteinuria with subclinical hypothyroidism were 27.00 (95%CI 1.69 to 17.7) and 19.80 (95%CI 1.94 to 201.63), respectively. Conclusion Subclinical hypothyroidism correlates with serum albumin level and proteinuria in nephrotic syndrome patients. Tha low serum albumin level has a high likelihood of subclinical hypothyroidism.